The Effect Of Employee Engagement On Turnover Intention: The Mediating Role Of Job Satisfaction At PT XYZ, A Healthcare Provider Company - Syah Fanissa, Raina; Indiyati, Dian (International Journal of Science, Technology & Management, 2025)
Employee engagement is a critical factor in managing human resources in the healthcare sector. Low engagement may reduce job satisfaction and increase turnover intention, affecting service quality and organizational stability. At PT XYZ, internal data show declining engagement and rising turnover intention in the past two years. This study aims to examine the effect of employee engagement on turnover intention, with job satisfaction as a mediating variable. Using a quantitative survey method, data from 131 permanent employees were analyzed with PLS-SEM. The expected result is that employee engagement negatively affects turnover intention, with job satisfaction mediating this relationship. Findings are expected to support policies to improve employee retention and satisfaction in healthcare services.